2016
DOI: 10.18203/2394-6040.ijcmph20161401
|View full text |Cite
|
Sign up to set email alerts
|

A study on social factors and magnitude of mental health problem among women with marital disharmony

Abstract: Marriage is an institution, the foundation of family life which in turn is the basic unit of a society. In India, arranged marriages stay put as the most favored option for most sections of society owing to cultural and religious beliefs. 1,2 Even then, in the recent changing times, a few cases of liberal mindedness are also seen. Marriage being the union of two people and more so, two families, requires a lot of adjustment from both sides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In one study females with marital disharmony were assessed and it was found that common reasons for disharmony were-dowry related and substance dependence. Depression was most commonly seen in these subjects [18].…”
Section: Depressionmentioning
confidence: 84%
“…In one study females with marital disharmony were assessed and it was found that common reasons for disharmony were-dowry related and substance dependence. Depression was most commonly seen in these subjects [18].…”
Section: Depressionmentioning
confidence: 84%